PENYAMBUTAN TAMU OLEH RESEPSIONIS DI FRONT OFFICE HOTEL NIAGARA PARAPAT KABUPATEN SIMALUNGUN PROVINSI SUMATRA UTARA - Marjuang H. Sinaga; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Welcoming guests by the receptionist is one of the services provided as a hotel service for guests for the satisfaction of guests. Friendly guests by the receptionist can give a good or bad impression of the first hotel service and the last impression of hotel services for their guests. This research was conducted at a four-star hotel (****), Niagara Parapat Hotel, in Simalungun Regency, North Sumatra Province. The purpose of this study is to find out how reception by reception and guest response to reception by receptionists at the front office of the Niagara Parapat hotel. The research method used in this study is a quantitative descriptive method to determine the responses of respondents by interviewing, questionnaire, observation and documentation data collection techniques. The results of this study, concluded that reception by the receptionist at the Niagara Parapat hotel is Excellent.  Keywords: Guest Welcome, Guest Response, Receptionist